Higgs production at the LHC: Updated cross sections at s=8 TeV - de Florian, D. (2012)
We present predictions for the inclusive cross section for Higgs boson production by gluon-gluon fusion in proton collisions at s=8 TeV. Our calculation is accurate up to next-to-next-to-leading order in QCD perturbation theory and includes soft-gluon effects up to next-to-next-to-leading logarithmic accuracy and two-loop electroweak corrections. The dependence on heavy-quark masses is taken into account exactly up to next-to-leading order and next-to-leading logarithmic accuracy, and a treatment of the Higgs boson line-shape is provided according to the complex-pole scheme. © 2012 Elsevier B.V.